2022
DOI: 10.1038/s41398-022-01813-4
|View full text |Cite
|
Sign up to set email alerts
|

Protracted abstinence in males with an opioid use disorder: partial recovery of nucleus accumbens function

Abstract: Opioid use disorder (OUD) affects more than 27 million people globally accounting for more than 300,000 deaths annually. Protracted abstinence among individuals with OUD is rare due to a high relapse rate among those not receiving medications for OUD. Extensive preclinical studies form the basis of the allostasis theory, which proposes long-lasting functional brain abnormalities that persist after opioid withdrawal and contribute to relapse. Few studies have tested the allostasis theory in humans using neuroim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For the present study, we used an instrumental reward learning and loss avoidance learning task that we have used for studies on depressive illnesses ( Johnston et al, 2015 ), opioid dependency ( Gradin et al, 2014 ; Tolomeo et al, 2022 ), and binge alcohol drinking ( Tolomeo et al, 2020 ; 2023 ). Subjects had to learn to choose between two pairs of nonsmoking-related visual stimuli to maximise rewards and avoid losses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the present study, we used an instrumental reward learning and loss avoidance learning task that we have used for studies on depressive illnesses ( Johnston et al, 2015 ), opioid dependency ( Gradin et al, 2014 ; Tolomeo et al, 2022 ), and binge alcohol drinking ( Tolomeo et al, 2020 ; 2023 ). Subjects had to learn to choose between two pairs of nonsmoking-related visual stimuli to maximise rewards and avoid losses.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects had to learn to choose between two pairs of nonsmoking-related visual stimuli to maximise rewards and avoid losses. The events of interest were the times when the subjects learnt the outcomes of their decisions, e.g., “you win” or “nothing.” As described in a series of previous studies, this contrast provides a non-invasive measure of brain reward function ( Steele et al, 2007 ; Gradin et al, 2014 ; Johnston et al, 2015 ; Tolomeo et al, 2022 ). It is important to note that the reward signal at the outcome time is different from the signal at the time the pairs of stimuli are presented, and a choice has to be made, the latter being the expected reward value signal ( Tolomeo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Thus, even in the absence of acute withdrawal, associations between relief from negative affect and prior substance use constitute a powerful ongoing motivationally salient stimulus for continued use. 183 , 184 Given this notion of addiction as both a reward deficit and stress surfeit problem, it is highly likely that both childhood maltreatment experiences and subsequent intimate partner violence further impact this process. 39 - 42 To the extent that these traumatic experiences pre-date substance use initiation, people may experience more brittle affect and emotional dysregulation at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Heroin addiction is characterized by excessive drug-seeking and drug-taking behaviours despite serious adverse consequences, and it manifests clinically as a chronic relapsing cycle of binging, intoxication, withdrawal and craving. [1][2][3] Functional magnetic resonance imaging (fMRI) studies have demonstrated an association between specific forms of addiction (e.g., substance use and behavioural) and abnormal func-tional connectivity between and within brain networks. 4,5 Among these addiction-related networks, a triple brain network comprising the default mode network (DMN), the salience network (SN) and the executive control network (ECN), which was proposed by Menon, 6 has received extensive attention in the context of heroin addiction.…”
Section: Introductionmentioning
confidence: 99%